The Hamburg/ESO R-process Enhanced Star Survey (HERES) - XI. the highly r-process-enhanced star CS 29497-004 - Hill, Vanessa; Christlieb, Norbert (Astronomy and astrophysics, 2017)
We report an abundance analysis for the highly r-process-enhanced (r-II) star CS 29497-004, a very metal-poor giant with solar system T eff = 5013 K and [Fe/H] = −2.85, whose nature was initially discovered in the course of the HERES project. Our analysis is based on high signal-to-noise ratio, high-resolution (R ~ 75 000) VLT/UVES spectra and MARCS model atmospheres under the assumption of local thermodynamic equilibrium, and obtains abundance measurements for a total of 46 elements, 31 of which are neutron-capture elements. As is the case for the other ~25 r-II stars currently known, the heavy-element abundance pattern of CS 29497-004 well-matches a scaled solar system second peak r-process-element abundance pattern. We confirm our previous detection of Th, and demonstrate that this star does not exhibit an “actinide boost”. Uranium is also detected (log ϵ (U) = −2.20 ± 0.30), albeit with a large measurement error that hampers its use as a precision cosmo-chronometer. Combining the various elemental chronometer pairs that are available for this star, we derive a mean age of 12.2 ± 3.7 Gyr using the theoretical production ratios from published waiting-point approximation models. We further explore the high-entropy wind model (Farouqi et al. 2010, ApJ, 712, 1359) production ratios arising from different neutron richness of the ejecta (Y e), and derive an age of 13.7 ± 4.4 Gyr for a best-fitting Y e = 0.447. The U/Th nuclei-chronometer is confirmed to be the most resilient to theoretical production ratios and yields an age of 16.5 ± 6.6 Gyr. Lead (Pb) is also tentatively detected in CS 29497-004, at a level compatible with a scaled solar r-process, or with the theoretical expectations for a pure r-process in this star.
Published online: 21 November 2017
Gesehen am 21.06.2018